The Threat to Cultural Heritage in Times of Conflict and Its Dynamic Relationship with Gulf Society - Amr Al-Azm (15445301) (2023)
Cultural heritage, both material and immaterial, is an important representation of a nation’s diverse cultures and vital to national identity. Yet this heritage is increasingly coming under threat from ongoing regional conflicts resulting in an unprecedented surge in looting and trafficking in cultural heritage materials throughout the region. Furthermore, social media has led to the exponential growth of this illicit trade of antiquities where an international network of traffickers, traders and terrorists utilize online platforms for the auctioning and sale of cultural goods. This paper seeks to address a number of questions pertaining to the evolving relationship of Gulf states and societies to cultural heritage (museums, private collections, etc.) and the international laws and conventions protecting them. The extent of trafficking that occurs in the region and changing attitudes to it. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_16